Noninvasive Assessment of Cardiovascular Autonomic Control in Pediatric Obstructive Sleep Apnea Syndrome - Zheng Lin; Chen, M.L.; Keens, T.G.; Davidson Ward, S.L.; Khoo, M.C.K. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2005)
Studies suggest that obstructive sleep apnea syndrome (OSAS) is causally related to abnormal cardiovascular autonomic control in adults, but this has not been established in pediatric OSAS. The goal of this study was to quantify autonomic system dysfunction, as manifested by cardiovascular response abnormalities, in children with OSAS. During wakefulness, we continuously measured the ECG, arterial blood pressure and airflow in each subject. These measurements were made during the following conditions: spontaneous breathing in the supine posture (baseline), spontaneous breathing in the standing posture (orthostatic stress); tracking of the subject's own prior spontaneous breathing pattern while supine (mental stress), and during a cold face challenge. Using spectral analysis and modeling techniques, we sought to computationally delineate the physiological mechanisms that mediate these abnormalities. Our preliminary results suggest that the autonomic effects of pediatric OSAS differ from those in adult in that parasympathetic activity remains relatively normal despite the elevated peripheral sympathetic drive